Health and production aspects of village based N'Dama cattle in The Gambia - Dwinger, R.H.; Agyemang, K.; Little, D.A.; Leperre, P.; Jeannin, P.; Bah, M.L.; Grieve, A.S. (Utrecht University, 1990)
Discusses health and production aspects of village based N'Dama cattle in The Gambia. Presents data on the monthly distribution of calving, average monthly weight and performance characteristics of N'Dama cows fed supplementary groundnut meal.